Dampak Covid 19 terhadap Kredit Bermasalah Pada Program Relaksasi Kredit PT. BRI KC Tuanku Tambusai - Misral Misral; Sri Rahmayanti (Akuntansi & Ekonomika, 2022)
Research aims to understand the factors that cause credit problems and efforts to overcome the credit so that it runs safely on the relaxation of PT Bank Rakyat Indonesia Tuanku Tambusai credit. Data comes from primary data, namely efforts to solve non-performing loans and secondary data, namely the number of admins of credit sections, books, articles, websites, research results related to the problem studied. Researchers collect data with interviews, observations and documentation. The findings in the study that the settlement of non-performing loans by negotiating with the extension of the credit term, the reduction of the rate, the reduction of principal arrears of credit and the addition of credit facilities are in accordance with OJK Regulation No.11 of 2020.